Support Services for Survivors of Extramarital Affairs: Lessons for Social Workers and Child Rights Advocates - Yahya Muhammed Bah (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Extramarital affairs remain a pervasive phenomenon across societies, with far-reaching negative socio-economic and political consequences for couples, children, and communities. Objective: The objective of this study was to systematically review the range of support services required by survivors of extramarital affairs and to synthesise knowledge that can inspire effective interventions. Method: A systematic literature review was conducted using multiple sources, including Google Scholar and other academic databases. Only peer-reviewed articles published after 2000 were included, except for seminal works providing essential conceptual foundations. In addition, publications from established international organisations with longstanding engagement in this area were critically appraised. Result: The findings indicate that survivors require diverse forms of support, such as disclosure, education and awareness programs, behavioural therapy, poverty and inequality alleviation, healthcare services, social welfare interventions, relationship satisfaction initiatives, group therapy, and counselling. Conclusion: This study concludes that holistic and multi-sectoral support services are essential to mitigate the long-term impacts of extramarital affairs. Contribution: The contribution of this review lies in consolidating fragmented knowledge, providing a comprehensive understanding of survivor needs, and offering evidence-based insights that can guide social workers, healthcare providers, and policymakers in designing effective interventions.